An Unexpected Cause of Reversible Dementia in an Elderly Patient: A Giant Cell Arteritis Case Report - Ghiletchi, Angela; Moniz, Wendy; Costal, Francisco; Barros, Leonilde; Miranda, Tiago; Cardadeiro, Diogo; Ramos, Diogo; Nazário Leão, Rodrigo (International Journal of Innovative Research in Medical Science, 2024)
Giant Cell Arteritis (GCA) is the most common systemic vasculitis in individuals over the age of 50, typically presenting with cranial symptoms such as headache and visual disturbances. However, GCA can present atypically with neuropsychiatric symptoms, which can mimic dementia, making diagnosis challenging, particularly in elderly patients. Here, we present the case of a 101-year-old female with a history of temporal arteritis who developed behavioural changes, agitation, and visual hallucinations. Initially misdiagnosed as dementia and treated with antipsychotic medications, the patient’s symptoms worsened. Upon hospital admission, laboratory investigations revealed elevated inflammatory markers (ESR 65 mm/h, CRP 53 mg/L), prompting a trial of corticosteroid therapy (prednisolone 60 mg daily). The patient showed marked improvement in neuropsychiatric symptoms, confirming the diagnosis of GCA. This case highlights the importance of considering reversible causes of dementia, such as GCA, in elderly patients with cognitive decline, especially when inflammatory markers are elevated and a history of vasculitis is present. Early diagnosis and treatment with corticosteroids can lead to significant clinical recovery and prevent irreversible complications.